A critical descriptive analysis of the role of track I and track II diplomatic interventions: the case of the Democratic Republic of Congo (1998-2002) - De Carvalho, Vanessa Roque (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.